Effects of the waterproofing additive on capillary absorption and porosity of the Self-Compacting concrete - Carrillo, Ana Victoria Torre (2023)
The objective of this research was to assess the impact of a waterproofing admixture on the porosity and capillary absorption of self-compacting concrete with water/cement ratios of 0.40, 0.45, and 0.50. The study began with the characterization of the component materials, followed by the calculation of six different mix designs, including three standard concrete mixtures and three concrete mixtures with the waterproofing admixture. In the fresh state, the temperature and fluidity of each mixture were measured. Thirty cylindrical specimens measuring 15x30cm were then produced and cured for 28 days following ASTM C-31 standards. Porosity and capillary absorption were determined according to ASTM C642. The results for porosity in the standard concrete samples with water/cement ratios of 0.40, 0.45, and 0.50 were 11.57%, 12.16%, and 13.06%, respectively. In contrast, the samples with the waterproofing admixture showed porosity values of 7.26%, 7.77%, and 8.06% for the same water/cement ratios, indicating an average decrease in porosity of 4.5%. As for capillary absorption, the standard concrete samples exhibited values of 5.2%, 5.3%, and 5.7%, while the samples with the waterproofing admixture showed values of 3.21%, 3.3%, and 3.5%. On average, the capillary absorption of the self-compacting concrete decreased by 2% with the addition of the waterproofing admixture. In conclusion, the waterproofing admixture effectively reduced both the porosity and capillary absorption of self-compacting concrete with water/cement ratios of 0.40, 0.45, and 0.50.